Research of Regenerative Braking Test Rig of Flywheel Energy Storage for Vehicular Application - Li Hongliang; Zhang Xinbin; Chu Jiangwei (Jixie chuandong)
According to the research situation of electric vehicle braking energy recovery,a new hybrid scheme of flywheel energy storage device coupling to vehicular powertrain is proposed. Three operation modes consist of brake energy recovery mode,storage energy output mode,recovery energy hold mode of flywheel energy storage device during vehicle operation process are presented. The vehicular flywheel energy storage device regenerative braking test rig and experimental system are designed,and the energy recovery rate is regarded as evaluation index to analyze and evaluate the energy recovery effect of flywheel energy storage device. The energy recovery tests under multiple vehicle speed are carried out by taking the rotational kinetic energy of flywheel to simulate the vehicle kinetic energy during braking under different speeds. The experimental results show that energy storage flywheel has energy balance in view of transmission ratio restriction during energy recovery storage process,and the average energy recovery rate is 25. 28%. The developed test rig is able to satisfy the control demand of regenerative braking system from the architecture to the control scheme.